The Generic Names of Meigen 1800 and Their Proper Application (Diptera). (2nd December 2014) - Stone, Alan
Abstract : Since the republication of a portion of Meigen‗s "Nouvelle classification des mouches a deux ailes (Diptera L.)" by Hendel (1908), in which he placed in synonymy many of the names proposed by Meigen in 1903, there has been divided opinion as to the names to be used for the genera involved. While many discussions of this problem have been published, it is thought advisable at the beginning of this paper to present a consideration of the arguments that have been offered as justification for the rejection of the names of Meigen 1800.